Alterations in cardiac morphology and function in elite multi-disciplinary athletes - Whyte, G.; Sharma, S.; George, K.; McKenna, W. J. (International Journal of Sports Medicine, 1999)
Early echocardiographic studies of left ventricular (LV) morphology and function focused on single discipline athletes, primarily endurance and strength trained. To date there are few studies examining multi-disciplinary trained athletes. The present echocardiographic study examined LV morphology and function in 18 elite triathletes (swimming, cycling, and running) and 11 elite modern pentathletes (running, swimming, shooting, fencing, and show-jumping) compared with age- and sex-matched controls. Elite triathletes demonstrated significantly (p < 0.05) increased LV wall thickness and cavity dimensions together with LV mass, both in absolute terms and scaled for body surface area, compared with controls. Elite modern pentathletes demonstrated significantly (p < 0.05) increased LV wall thickness with a non-significant increase in LV internal diameter. Despite significant LV enlargement, the distribution of hypertrophy and diastolic filling indices were normal in both triathletes and modern pentathletes and significantly increased in the triathletes. It is concluded that multi-disciplinary training results in variations in LV morphology. The inciting stimulus resulting in LV enlargement in triathletes is associated with prolonged endurance activity, together with an isometric component accompanying cycling. In contrast, elite modern pentathletes experience a reduced endurance component combined with a high isometric component associated with fencing.